PSII-8 Effects of polyamines and trenbolone acetate on proliferation rates of murine myoblasts. (5th December 2019) - Smith, Laura A; Ineck, Nikole E; Udy, Brynne A; Erickson, Chris L
Abstract: Androgens, such as testosterone, increase growth of skeletal muscle, although the exact mechanism through which these molecules function to increase growth of skeletal muscle remains unknown. Recent research indicates that one of the mechanisms through which androgens improve skeletal muscle growth is by modulation of the polyamine biosynthetic pathway. Polyamines are naturally occurring amino acid derivatives that are found in many whole foods and are potent stimulators of cell proliferation in several different cell types. However, the effect that polyamines have on growth of skeletal muscle has not been well characterized. The objective of this study was to investigate the effect that trenbolone acetate (a testosterone analog, TBA), polyamines (putrescine, spermine, and spermidine), and polyamine precursors (methionine and ornithine) have on proliferation of Sol8 and C2C12 murine myoblasts. Cultures were treated with 1% fetal bovine serum and 10 nM TBA, 10 mM methionine, 8 mM ornithine, 3 mM putrescine, 1.5 mM spermidine, or 0.5 mM spermine and proliferation rates were compared to a control (1% fetal bovine serum). Sol8 cells that were treated with 10 nM TBA and 10 mM methionine had increased (P < 0.001) proliferation rates compared to the control. C2C12 cells that were treated with 10 nM TBA, 8 mM ornithine, or 1.5 mM spermidine had increased (P < 0.001) proliferation rates compared to the control. This research demonstrates that TBA, some polyamines, and some polyamine precursors increase proliferation of myoblasts and thus, are capable of enhancing the rate of skeletal muscle growth. However, further research is needed to understand the relationship between androgens and the polyamine biosynthetic pathway relative to skeletal muscle growth.